Formation of younger students core competencies in learning mathematics - Mukhametzhanova, A.O.; Zhapanova, R.N. (Ye.A.Buketov Karaganda State University Publishing house, 2015)
The article presents a method for the formation of younger students core competencies in math class. The essence, structure, functions, development of competence of younger students, provides methods for designing and teaching conditions. Emphasizes the importance of building students' skills of academic work rational organization of. Discloses a general training and skills and their combination provides a reliable basis for further training of pupils cognitive activity, they determine the acquisition of deep and tight knowledge. It is told about the feasibility of competence in mathematics lessons in elementary school. The question of the students key competence formation of students is regarded with the means of innovative educational technologies. The methods for facilitating, are presented, as the effective formation of the primary school students competence.
Кіші жас оқушыларына математика сабақтарында негізгі құзыреттіліктерді қалыптастыру
Формирование ключевых компетенций в процессе обучения математике младших школьников
Keywords: modernization of education; training and cognitive competence; basic competence; competencebased approach; information competence; humanization; democratization; the methodology of thinking; intensification; formation competencies